Prelamination of the latissimus dorsi flap for reconstruction in head and neck surgery. Issue 9 (September 2019) - Jehn, P.; Zimmerer, R.; Dittmann, J.; Winterboer, J.; Gellrich, N.-C.; Tavassol, F.; Spalthoff, S.
Abstract: Free microsurgical tissue transfer of the latissimus dorsi flap may be indicated for the restoration of intra- and extraoral defects, especially when a large-sized skin island flap is required. In many cases, use of the latissimus dorsi flap for coverage of large-sized intraoral defects results in bulkiness due to the proportion of subcutaneous fat. Prelamination of free flaps appears to be a promising technique to overcome this flap bulkiness. This modification in flap design could improve the postoperative functional outcome, as well as reduce donor site morbidity. This article presents four novel clinical cases, in which the patients underwent prelamination of the latissimus dorsi flap with local skin grafts during oral cancer treatment in order to reduce the thickness of the free flap and allow tension-free primary closure of the donor site. These attempts successfully covered large-sized intraoral defects, achieving good functional outcomes with minimal donor site morbidity.